Penerapan Teknik Thought Stopping Untuk Mengurangi Kecemasan Berbicara Di Depan Kelas Pada Siswa SMK Negeri 4 Takalar - Nur Magfirah; Abdullah Sinring; Fitriana Fitriana; Siska Putri Ayu (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2026)
This study aims to determine whether the application of the thought-stopping technique can alleviate students' nervousness when speaking in front of the class at SMK Negeri 4 Takalar. Employing a quantitative experimental approach, this research utilized a non-equivalent control group pretest-posttest design. The population consisted of 31 students diagnosed with classroom speaking anxiety. A sample of 20 students was selected and divided into two groups of 10: an experimental group and a control group. Data were collected by measuring students' anxiety levels in front of the class both before and after the intervention. The data were then analyzed using descriptive and inferential statistics, specifically the independent samples t-test. The results indicated that prior to the intervention, speaking anxiety levels ranged from moderate to high. Following the thought-stopping therapy, the experimental group exhibited a significant reduction in anxiety levels compared to the control group, which received no intervention. The thought-stopping technique comprises five steps: (1) the counselor and client collaboratively identify and select the target thought to be addressed; (2) the client closes their eyes and visualizes a scenario in which the target thought is likely to occur; (3) the target thought is interrupted by a verbal "stop" command; (4) the negative thought is replaced with a more positive alternative; and (5) homework assignments and follow-up sessions are provided. The independent samples t-test revealed a significant difference between the experimental and control groups, yielding a t-value of 7.639 and a significance level of p < 0.001 (two-tailed). These findings indicate that the implementation of the thought-stopping technique effectively reduces the level of nervousness among students at SMK Negeri 4 Takalar when speaking in front of the class.